Program of the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities - International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Abstracts of parallel sessions are included. Symposium includes 4 Plenary sessions, and parallel sessions covering Wildlife Management; Sustainable Use of Wildlife; and IUCN 2nd African Buffalo Symposium.
Wildlife - the key to prosperity for rural communities
9th international wildlife ranching symposium
9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.